Poppers: legal highs with questionable contents? A case series of poppers maculopathy. Issue 11 (10th April 2017) - Rewbury, Rebecca; Hughes, Edward; Purbrick, Robert; Prior, Stephen; Baron, Mark
Abstract : Background: Poppers are volatile alkyl nitrite compounds that are inhaled to enhance sexual experience and for their psychoactive effects. A less well-known side effect is foveal maculopathy, which has emerged following changes in their chemical composition. It is unclear if certain individuals are more susceptible to retinal damage or if there is a relationship between pattern of inhalation and brands used. Methods: A case series of 12 patients presenting to Sussex Eye Hospital, Brighton, with poppers-related visual impairment. Follow-up data were available in 10 cases, at a median time interval of 5 months (range 0–31 months). Eight samples of poppers were analysed using proton nuclear magnetic resonance spectroscopy. Results: Patients presented with disrupted central vision occurring soon after inhalation. All demonstrated disruption of the inner segment/outer segment junction on spectral domain optical coherence tomography. Six of the brands implicated in causing visual symptoms contained isopropyl nitrite, while Jungle Juice Plus varieties, used without side effects in one case, contained amyl nitrite, 2-methyl butyl nitrite and isobutyl alcohol. In general, symptomatic resolution, alongside partial, if not full, recovery of foveal architecture was observed following abstention. Discussion: On the basis of the products tested here, it seems that isopropyl nitrite is toxic to the fovea and can cause significant visual disturbance. The production of poppers is unregulated and their popularity is concerning, particularly given their exemption from the Psychoactive Substances Act 2016, which might suggest that they are harmless chemicals.